2014
DOI: 10.1037/sgd0000052
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of stigma and self-reported school engagement in same-sex couples with young children.

Abstract: Little research has explored same-sex parents’ school engagement, although there is some evidence that same-sex parents’ perceptions of openness versus exclusion in the school setting –as well as other interrelated contexts – may have implications for their relationships with and perceptions of their children’s schools. The current cross-sectional study used multilevel modeling to examine the relationship between same-sex parents’ perceptions of stigma in various contexts and their self-reported school involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 54 publications
(107 reference statements)
1
27
1
Order By: Relevance
“…Perhaps LG parents also experience less trust that schools (which are frequently heteronormative in their policies and practices, and employ staff who lack comfort with LG-parent families; Goldberg and Smith, 2014) will effectively support their families, and are less likely to turn to them if their child is mistreated. At the same time, research on LG parents of young children suggests that they are highly involved at school, in part because they hope that their proactive advocacy will facilitate more favorable treatment (Goldberg and Smith, 2014;Goldberg et al, 2017). In turn, LG parents may indeed turn to school-based supports amidst child victimization, especially if they are highly involved and therefore expect positive treatment.…”
Section: Predictors Of Parents' Responses To Victimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps LG parents also experience less trust that schools (which are frequently heteronormative in their policies and practices, and employ staff who lack comfort with LG-parent families; Goldberg and Smith, 2014) will effectively support their families, and are less likely to turn to them if their child is mistreated. At the same time, research on LG parents of young children suggests that they are highly involved at school, in part because they hope that their proactive advocacy will facilitate more favorable treatment (Goldberg and Smith, 2014;Goldberg et al, 2017). In turn, LG parents may indeed turn to school-based supports amidst child victimization, especially if they are highly involved and therefore expect positive treatment.…”
Section: Predictors Of Parents' Responses To Victimizationmentioning
confidence: 99%
“…Although research has gradually begun to address the experiences of LGparent families (Goldberg, 2010), rarely has it considered their intersections with the school context. Studies of LG parents of young children have examined their school decisions (Goldberg et al, 2018) and school involvement (Goldberg and Smith, 2014;Goldberg et al, 2017) and several studies of LG-parent families with school-aged children have explored children's experiences with teasing and victimization (Bos and van Balen, 2008;Kosciw and Diaz, 2008;Rivers et al, 2008;Farr et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a study of how the LGB community changed after gaining a legal protection in Colorado found that involvement declined because they had won what they were fighting for (Russell, Bohan, McCarroll, & Smith, 2011). Looking specifically at parents, Goldberg and Smith (2014) found that LGB parents were more involved in their children's schools when they perceived those schools as less supportive. Also, Holman and Oswald (2011) found that negative attention regarding LGB parents' sexuality was most likely to occur in organizational settings such as schools, hospitals, courtrooms, and workplaces.…”
Section: Nonmetropolitan Community Characteristicsmentioning
confidence: 99%
“…For example, lesbian and gay parents reported a tremendous sense of relief and family security associated with gaining the right to adopt in Florida (Goldberg, Moyer, Weber, & Shapiro, ). Further, adoptive sexual minority parents who perceived that their neighborhoods were more “gay‐friendly” were less likely to perceive that instances of mistreatment were motivated by anti‐LGB bias (Goldberg & Smith, ). Similarly, in an ethnography of Black gay women in New York City, most of whom were mothers, Moore () described how the women sought out specific community settings because they provided support for the mothers' identities and families.…”
Section: Review Of Literaturementioning
confidence: 99%
“…), including LG adoptive parent families (Lamb, 2012;Farr, 2017). Even so, in the US, adoptive parents often face stigma (e.g., concerns about parenting ability; Miall, 1987) related to "non-traditional" family structures (i.e., differing from married heterosexual parents with biologically related children), and LG adoptive parents often face additional stigma based on sexual identity (Goldberg, 2009;Herek, 2010;Goldberg and Smith, 2014;Lo et al, 2019). For example, the question of whether samegender couples could raise children as effectively as do differentgender couples was a central debate in the ruling for marriage equality in the US, a ruling that held important legal implications about whether (married) same-gender couples could jointly adopt children (American Psychological Association [APA], 2015;Obergefell v. Hodges, 135 S. Ct. 2584, 2015.…”
Section: Introductionmentioning
confidence: 99%